Economic Feasibility of Ginger Emprit Extract Drink (Zingiber officinale Var. Amarum) using CMC Stabilizer - Ahmad Farhan; Anwar Kasim; Rini B (Andalasian International Journal of Agriculture and Natural Sciences (AIJANS), 2023)
The tempe industry is one of the most numerous industries in Indonesia, so there is a high opportunity for making tempeh juice in the tempe industry. The application of tempeh in the manufacture of tempeh essence drink with emprit ginger extract is expected to provide benefits to the tempe industry in Indonesia. Tempe juice drink is one of the processed food products made from tempeh. Tempe juice drink is added with emprit ginger extract to remove the unpleasant aroma from tempeh and give flavor to the tempeh juice drink. On manufacture Tempe juice drink Emprit ginger extract need addition material CMC stabilizer for increase stability and viscosity product . Study This aim To determine the economic feasibility, an economic analysis was carried out regarding the feasibility of applying tempeh juice in the tempe industry. The research begins with making assumptions and analyzing the parameters, components and cost structure, the need for investment funds and working capital. This parameter calculates projected production, revenue and cash flow. Determination of the economic feasibility of the Tempe juice drink with Emprit ginger extract with the Net Present Value (NPV), Incremental Rate of Return (IRR), Net B/C and Pay Back Period (PBP). The assumption of drinking tempeh juice with emprit ginger extract in a year is 45600 bottles at a price of IDR 10,000.00 / bottle . The proportion of capital comes from 60% own capital and 40% credit. The average operational cost per year is IDR 278.606.467.00, variable costs Rp 233.606.467.00, and a flat fee of Rp 45.000.000.00 . Average income per year Rp 319.200,000.00 while spending Rp 304.017.802.00.  The profit earned is Rp 151.982.198. Sales profit 2 8.33 % with 15% tax per year. This business BEP occurs in sales with an average value of Rp. 151.982.198 or 33,33 % of production capacity per year. The results showed that the NPV was Rp 156.180.415, IRR is 53 %, and Net B/C is 1.82 times. Based on existing criteria or assumptions, this business is feasible to run with PBP for two years, or the capital invested in this business can be returned before the project ends (3 many years).